Endocrine and metabolic comorbidities in juvenile-onset systemic lupus erythematosus - Park, Su Jin; Ahn, Moon Bae; Jeong, Dae Chul (Frontiers in Medicine, 2025)
Background and aimsJuvenile-onset systemic lupus erythematosus (JSLE) is a chronic autoimmune disease affecting individuals under 18, causing multi-system impairment. Patients with JSLE exhibit more severe disease when compared to patients with adult-onset SLE. This study aimed to evaluate the prevalence of endocrine and metabolic comorbidities in patients with JSLE, and analyze the factors associated with each comorbidity.MethodsAnthropometric, clinical, laboratory data, and the details of glucocorticoids and disease-modifying anti-rheumatic drugs use were collected.ResultsA total of 57 patients with JSLE (48 girls and 9 boys) were included in this study. Endocrine and metabolic comorbidities were observed in 64.9% of the patients. The most prevalent comorbidities were dyslipidemia (40.4%), being overweight or obese (26.3%), subclinical hypothyroidism (24.6%), autoimmune thyroid disease (AITD) (21.1%), and low bone mass (20.9%). The risk of dyslipidemia and AITD increased in patients who were overweight or obese. The risk of being overweight or obese was associated with skin involvement at diagnosis and rheumatoid factor positivity. Younger age at diagnosis and longer duration of glucocorticoid exposure increased the risk of low bone mass. The overall prevalence of endocrine and metabolic comorbidities was associated with short stature at diagnosis, being overweight or obese at follow-up, skin involvement at diagnosis, and rheumatoid factor positivity.ConclusionPatients with JSLE have higher burdens of endocrine and metabolic comorbidities and should be routinely monitored. Prevention of obesity may be helpful in lowering the risk of comorbidities.